2020
DOI: 10.1039/d0ew00539h
|View full text |Cite
|
Sign up to set email alerts
|

Regularized regression analysis for the prediction of virus inactivation efficiency by chloramine disinfection

Abstract: The sparse modeling methods using water quality information as explanatory variables enable us to appropriately predict virus inactivation efficiency in wastewater treatment plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Many techniques of artificial intelligence (AI), including multiple linear regression (MLR), 7 the artificial neural network (ANN), [8][9][10] and the support vector machine (SVM), [11][12][13][14] have been applied to the process of water treatment. 8,[15][16][17][18][19][20][21][22][23] Many hybrid AI technologies used to determine the quality of water have also emerged in recent years, and have been used for making observations based on remote sensing, predicting the distribution of the water plant, and decision making. 24,25 A number of models have been applied to predict the turbidity of the effluent [26][27][28][29][30][31] and the requisite coagulant dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques of artificial intelligence (AI), including multiple linear regression (MLR), 7 the artificial neural network (ANN), [8][9][10] and the support vector machine (SVM), [11][12][13][14] have been applied to the process of water treatment. 8,[15][16][17][18][19][20][21][22][23] Many hybrid AI technologies used to determine the quality of water have also emerged in recent years, and have been used for making observations based on remote sensing, predicting the distribution of the water plant, and decision making. 24,25 A number of models have been applied to predict the turbidity of the effluent [26][27][28][29][30][31] and the requisite coagulant dosage.…”
Section: Introductionmentioning
confidence: 99%
“… Kadoya et al. (2019 and 2020) previously proposed the concept of predictive water virology and reported that the predictive inactivation models, based on hierarchical Bayesian modeling (HBM) and regularized regressions, flexibly correspond to the changes and variety in water quality parameters among WWTPs ( e.g., seasonal variation). Predictive water virology can help us understand the required operational conditions to achieve the target LRV, in which there is no gap between the predicted and target LRVs.…”
Section: Introductionmentioning
confidence: 99%